2003
DOI: 10.1128/jvi.77.15.8249-8255.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Mice with Bacteria Carrying a Cloned Herpesvirus Genome Reconstituted In Vivo

Abstract: Bacterial delivery systems are gaining increasing interest as potential vaccination vectors to deliver either proteins or nucleic acids for gene expression in the recipient. Bacterial delivery systems for gene expression in vivo usually contain small multicopy plasmids. We have shown before that bacteria containing a herpesvirus bacterial artificial chromosome (BAC) can reconstitute the virus replication cycle after cocultivation with fibroblasts in vitro. In this study we addressed the question of whether bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…This was also shown by other groups (10,12,15,21,32) but was never addressed, although it stood in marked contrast to the high salivary gland titers observed when BALB/c mice were infected with MCMV strains not cloned as BACs (17,22,28,39). To find out whether this phenotype of the pSM3fr-derived virus was due to genomic differences between the MCMV Smith strain and the pSM3fr genome, we sequenced the complete genomes of pSM3fr, two independent pSM3fr-derived mutants (pSM3fr-⌬m157-⌬M27 and pSM3fr-⌬loxP) and a virus stock derived from pSM3fr-⌬m157-⌬M27.…”
Section: Sequence Divergency Of Psm3fr and Psm3fr-derived Virussupporting
confidence: 76%
See 1 more Smart Citation
“…This was also shown by other groups (10,12,15,21,32) but was never addressed, although it stood in marked contrast to the high salivary gland titers observed when BALB/c mice were infected with MCMV strains not cloned as BACs (17,22,28,39). To find out whether this phenotype of the pSM3fr-derived virus was due to genomic differences between the MCMV Smith strain and the pSM3fr genome, we sequenced the complete genomes of pSM3fr, two independent pSM3fr-derived mutants (pSM3fr-⌬m157-⌬M27 and pSM3fr-⌬loxP) and a virus stock derived from pSM3fr-⌬m157-⌬M27.…”
Section: Sequence Divergency Of Psm3fr and Psm3fr-derived Virussupporting
confidence: 76%
“…This was also observed when pSM3fr-derived viruses were characterized in vivo (10,12,15,21,32) and stood in marked contrast to high salivary gland titers obtained after infection with MCMV strains not cloned as BACs (17,22,28,39). We could restore the phenotype of high virus titers in salivary glands by repairing the pSM3fr mutation and thus provide evidence that pSM3fr-derived virus shows an attenuated growth phenotype in salivary glands due to a mutation in MCK-2.…”
Section: Discussionmentioning
confidence: 69%
“…After mice were infected, their weight loss was monitored daily. At 16 weeks p.i., titers of virus-specific antibodies in sera of immunized mice were determined by indirect enzyme-linked immunosorbent assay (ELISA), as described previously (18). In brief, plates were coated with lysates from MCMV-infected MEF as the source of antigen or with uninfected MEF as the background control.…”
Section: Methodsmentioning
confidence: 99%
“…3,9,11 In vivo, E. coli has been used as vector for DNA vaccines by intramuscular, intraperitoneal or subcutaneous administrations. 12,13 Here, we explored the ability of not genetically modified L. lactis to deliver plasmid in vivo to mice. We showed that oral administration of lactococci carrying a BLG eukaryotic expression plasmid induces a local production of BLG in the small intestine.…”
Section: Introductionmentioning
confidence: 99%